2010
DOI: 10.1007/s11145-010-9277-4
|View full text |Cite
|
Sign up to set email alerts
|

Do bilingual children possess better phonological awareness? Investigation of Korean monolingual and Korean-English bilingual children

Abstract: This study examined whether there are bilingual advantages in terms of phonological awareness (PA) for children acquiring two phonologically and orthographically different alphabetic languages and investigated the emergent literacy factors that explain variances in their PA, in comparison to monolingual children. The study participants comprised seventy 5-to 6-year-old Korean-English bilingual children who had attended English-medium kindergartens for at least 2 years and fifty-six Korean monolingual children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
0
28
3
2
Order By: Relevance
“…Specifically, there is evidence for a bilingual advantage in Russian-Hebrew bilinguals relative to Hebrew monolinguals (Eviatar & Ibrahim, 2000; Ibrahim, Eviatar, & Aharon-Peretz, 2007), Korean-English bilinguals relative to Korean monolinguals (Kang, 2012), English-Greek bilinguals relative to English monolinguals (Loizou & Stuart, 2003) and Putonghua-Cantonese bilinguals relative to speakers of Putonghua and Cantonese (Dodd et al, 2008). Similarly, Chen and colleagues showed that English instruction enhanced the development of phonological awareness skills in Chinese as revealed by performance of Chinese speakers who received English instruction or not (Chen, Xu, Nguyen, Hong, & Wang, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, there is evidence for a bilingual advantage in Russian-Hebrew bilinguals relative to Hebrew monolinguals (Eviatar & Ibrahim, 2000; Ibrahim, Eviatar, & Aharon-Peretz, 2007), Korean-English bilinguals relative to Korean monolinguals (Kang, 2012), English-Greek bilinguals relative to English monolinguals (Loizou & Stuart, 2003) and Putonghua-Cantonese bilinguals relative to speakers of Putonghua and Cantonese (Dodd et al, 2008). Similarly, Chen and colleagues showed that English instruction enhanced the development of phonological awareness skills in Chinese as revealed by performance of Chinese speakers who received English instruction or not (Chen, Xu, Nguyen, Hong, & Wang, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of school readiness and academic achievement, some research has focused predominantly on metalinguistic awareness, but in addition examined aspects of school readiness such as early literacy skills including letter, syllable and word identification, reading, and arithmetic skills (Dixon, 2010; Kang, 2012; Lesaux & Siegel, 2003; Lesaux, Rupp, & Siegel, 2007; Lindsey et al, 2003; Macaruso & Rodman, 2011; Manis, Lindsey, & Bailey, 2004; Nakamoto, Lindsey, & Manis, 2010; Paéz, Tabors, & López, 2007; Yeong & Liow, 2011). Results from metalinguistic tasks are reported in more detail in the previous section on phonological awareness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings demonstrated a significant positive correlation between phonological skills in first language and the same skills in the second language, in addition of significant positive correlation between phonological skills in Hebrew and text reading and pseudo-word reading in English. Identical findings were revealed between Korean, considered as an alphabetic language, and English (Chiappe, Glaeser, & Ferko, 2007;Kim, 2009;Kang, 2012;McBride-Chang et al, 2005;Wang, Cheng, & Chen, 2006). According to these studies, there is cross-linguistic transfer of phonological awareness in spite of the differences in phonological representation between the two languages.…”
Section: Phonological Awarenessmentioning
confidence: 79%
“…Potential If the stimuli used in the NRT and KNRT are eventually proven to be equivalent, another possible reason for the better KNRT results is the influence of the very simple, transparent, and regular letter to sound patterns in Korean. Children who are able to identify the individual letters of the Korean alphabet can sound out most syllables without much difficulty (Kang, 2012). This characteristic of Korean may allow the participants who were able to read and write in Korean, even at a basic level, to more easily store and process Korean phonological information during the task.…”
Section: Performance Difference Between English and Korean Language-bmentioning
confidence: 99%